Методи захисту інформації від витоку каналами стільникового зв'язку - Павлов, В. В. (ХНУРЕ, 2024)
The paper discusses passive and active methods of protecting information in cellular communication channels. Methods using cryptographic algorithms for encrypting speech information are promising. It has been established that the most effective is the integrated use of the considered methods.
Keywords: каналам стільникового зв'язку; захист інформації від витоку